Evaluating the Influence of Problem-Based Learning on High School Students’ Mathematics Performance - Pascal; Tan Hian Nio; Simbolon, Kerdid (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This research examines the influence of the Problem-Based Learning (PBL) model on the mathematics learning outcomes of Grade X students at SMAN 71 Jakarta. The study was conducted in response to students’ low achievement in mathematics and the learning difficulties commonly associated with conventional, teacher-centered instruction. A quantitative method with a quasi-experimental design was employed, involving two Grade X classes selected through purposive sampling: one experimental class (X-B) and one control class (X-C), each comprising 36 students. Students’ learning outcomes were measured using expert-validated pretest and posttest instruments. The collected data were analyzed using a series of statistical procedures including validity, reliability, normality, homogeneity tests and independent samples t-test using SPSS version 26. The analysis showed a significance value of 0.004 (p < 0.05) and the calculated t-value was 2.946 which is greater than the critical t-value of 1.994. These results indicate that the use of PBL model has led to a statistically significant improvement in the learning outcomes of students in mathematics. Furthermore, students who learned through PBL showed greater engagement and achieved higher scores than those who received conventional instruction.